2016
DOI: 10.1111/trf.13794
|View full text |Cite
|
Sign up to set email alerts
|

Ferric carboxymaltose reduces the number of red blood cell units transfused and allows transfusion independence to be obtained in patients with iron deficiency anemia secondary to gastrointestinal chronic blood loss

Abstract: In patients with IDA secondary to CBL, FCM significantly reduces the need of transfusions and achieves transfusion independence in half of the cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…According to McDonald et al, iron replacement therapy should be considered preferable to blood transfusions to manage anaemia resulting from HHTrelated haemorrhage (3) . Several studies demonstrated that intravenous iron supplementation is safe, cost-saving and reduces transfusion requirements and the percentage of transfusion-dependent patients (34)(35)(36)(37)(38) . This is the reason why the grading scale proposed by Al-Deen and Bachmann-Harildstad in 2008, even if is commonly used and easy to understand for the patients, may be surpassed by the FID score.…”
Section: Discussionmentioning
confidence: 99%
“…According to McDonald et al, iron replacement therapy should be considered preferable to blood transfusions to manage anaemia resulting from HHTrelated haemorrhage (3) . Several studies demonstrated that intravenous iron supplementation is safe, cost-saving and reduces transfusion requirements and the percentage of transfusion-dependent patients (34)(35)(36)(37)(38) . This is the reason why the grading scale proposed by Al-Deen and Bachmann-Harildstad in 2008, even if is commonly used and easy to understand for the patients, may be surpassed by the FID score.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, administration of i.v. iron can reduce the amount of red blood cell transfusions needed, helping to overcome IDA (20). In addition, transfusion should be administered cautiously, as other comorbidities, such as ischemic heart disease, could influence the outcome (21).…”
Section: Discussionmentioning
confidence: 99%
“…Other limitations to oral iron therapy are low levels of adherence, lack of suitability for patients with severe bleeding or continuous occult blood loss, the excessive time (months) required to replenish iron stores, and the lack of clarity regarding total costs, which may be higher than initially expected when absenteeism/presenteeism considerations are also taken into consideration. Newer intravenous iron compounds are considered safer than blood transfusion, have fewer GI side effects than oral iron (99,100), and are also associated with improved/guaranteed adherence (66,90,93,100,101). These compounds also provide the total iron dose required (often in a single infusion), quickly increase hemoglobin levels, and promote more effective replenishment of iron stores in comparison with oral iron (66,90,93,(100)(101)(102)(103).…”
Section: Advantages and Limitations Of Oral And Intravenous Iron Admi...mentioning
confidence: 99%
“…Newer intravenous iron compounds are considered safer than blood transfusion, have fewer GI side effects than oral iron (99,100), and are also associated with improved/guaranteed adherence (66,90,93,100,101). These compounds also provide the total iron dose required (often in a single infusion), quickly increase hemoglobin levels, and promote more effective replenishment of iron stores in comparison with oral iron (66,90,93,(100)(101)(102)(103). Much of the data supporting the efficacy and safety of intravenous iron in patients with GI bleeding come from studies of ferric carboxymaltose (FCM) (32,90,100,101).…”
Section: Advantages and Limitations Of Oral And Intravenous Iron Admi...mentioning
confidence: 99%